Community-based interventions for health promotion and disease prevention in noncommunicable diseases: A narrative review - Phinse Mappalakayil Philip; Srinivasan Kannan; Neetu Ambali Parambil (Wolters Kluwer Medknow Publications, 2018)
PURPOSE: Noncommunicable disease (NCD) prevention is emerging as a public health priority in developing countries. For better health outcome in these countries, it is necessary to understand the different community-based interventions developed and implemented across the world. OBJECTIVE: The objective of the current review is to identify the best strategies used in community-based health intervention (CBHI) programs across the world. MATERIALS AND METHODS: For review, we searched in PubMed and Google Scholar with the keywords "community based," "health interventions," "health promotions," "primary prevention," chronic diseases," "lifestyle-related diseases," and "NCD." Data were extracted using predesigned data extraction form. CBHI studies detailing their intervention strategies only were included in the review. RESULTS: Out of 35 articles reviewed, 14 (40%) were randomized control trials, while 18 (51.4%) were quasi-experimental design. Individual level (n = 14), group level (n = 5), community level (n = 6), and policy level (n = 4) intervention strategies were identified. Twenty-three (64%) studies were based on interventions for 1 year and above. Twenty-eight (80%) studies were intervened among specific populations such as Latinos and so on. CONCLUSION: Successful programs advocate for a package or a chain of interventions than a single intervention. The type of interventions at different levels, namely individual, group, community, and policy levels vary across studies, but individual, and group level interventions are more frequently used.